The role of open innovation and a normalizing mechanism of social capital in the tourism industry - Sanmugam Annamalah; Pradeep Paraman; Selim Ahmed; Rajinder Dass; Ilham Sentosa; Thillai Raja Pertheban; Farid Shamsudin; Baharudin Kadir; Kalisri Logeswaran Aravindan; Murali Raman; Wong Chee Hoo; Prakash Singh (Journal of Open Innovation: Technology, Market and Complexity, 2023)
Social considerations and potential for innovation in resource and technological exploitation processes have dominated traditional ideas of regional development. Similar to how regional economic progress is sometimes expressed in terms of job creation and rising property prices. An alternate viewpoint contends that the business community must be included into construction and planning strategies to counterbalance the conventional economic perspective since this approach often overlooks the social and community components of tourist development. This study makes the case that encouraging creativity in regional development (ASEAN) entails much more than just consulting the local tourist operators, but consideration should be given to regional open innovation concept. Although tourism development may be carried out in a fashion that enhances innovation, but it also requires a certain degree of external country partner (open innovation) so that it can serve its intended purpose as a tool for regional development and even contribute to the economy. The main ideas of human capital, structural capital, relational capital is discussed in this study. It does so in the framework of local tourist development, as well as the ideas of innovative development systems and sustainable development. The interplay of various kinds of social capital and various innovations in the growth of tourism that is both bridging and bonding is examined in this study. Increasing social capital shouldn't be seen as a quick fix to increase tourism. Thus, it may be claimed that regional policies focused at supporting non-traditional kinds of innovation should reflect the need of building and sustaining specific types of connectivity, namely social capital bridges.